Improving students' speaking skills in an academic English course (Journal of Educational Sciences, 2021)
This article summarizes the results of teaching Academic English course to the first year Intermediate level students. The article encompasses the activities for improving the speaking skills of learners. As re- quired in the Academic English curriculum, optimizing the speaking skills of students is of those in macro skills that should be focused and enhanced with the aid of myriads of teaching tools. There were four In- termediate groups with a total of 32 students. Speaking tests were included in the first attestation midterm exam and final examination. Practice has shown that students also need to get rid of the fear of speaking in English, thereby helps to minimize or completely eliminate the fear associated with speaking English, which means constant and confident practice in the learning environment and beyond using various tech- nical tools when studying or teaching English. The subject of the research is the improvement of speech skills among first year students, where students, learning a new vocabulary, train their speech skills during the semester. The study guidelines, various platforms for learning and teaching were used for the research. The study was conducted at one of the higher educational institutions of the city of Almaty, the Inter- national University of Information Technology. The results showed that thirty-two students had better results in the final exam than the midterm exam.Key words: teaching foreign languages, speaking skill, assessment.